Criação de valor ao cliente por meio da expansão da oferta de serviços - Arcari, Carlos Victor (2018)
Alpha CargoLog Transportes e Serviços Ltda – subsidiary Brusque-SC, the company that is the focus of this work, is a road cargo carrier that has difficulty growing in the face of an extremely competitive market. Amid this unfavorable scenario, the company received from its major customers, the request for extension in the provision of logistics services, in addition to the transportation already carried out. With that, attempts were made to understand the market in which Alpha CargoLog is inserted, in order to identify the possible opportunities. The goal of this work is to create superior value to customers, by expanding the service offering, in order to enable the growth of Alpha CargoLog - subsidiary Brusque-SC. The work follows the line of value creation and marketing of services that contrasts with the reality of the organization. Based on the understanding and the opportunity diagnosis, a proposal was developed to explore the opportunity, which occurred through the opening of a new business unit that will offer new logistics services, validated by the project's feasibility and financial analysis. This work presents a disruptive innovation in the Alpha CargoLog market, within the logistics segment. The integration of logistic operator services with transporter proved to be challenging to manage the complexity involved. It was necessary to find a new physical space, invest in structure and technology, develop and train a new team, develop partnerships and, finally yet importantly, sell and validate with the market the new integrated logistics services. The project is fully replicable in other companies and regions, wherein port areas tend to be more propitious for the application of this work. Large industrial centers can also be an opportunity to be explored, with companies that strategically outsource their entire logistics operation.